Blink reflex: comparison of latency measurements in different human races - Kimaid, Paulo Andre Teixeira [UNESP]; Resende, Luiz Antonio de Lima [UNESP]; Castro, Heloisa Amélia de Lima; Bérzin, Fausto; Barreira, Amilton Antunes (Academia Brasileira de Neurologia (ABNEURO), 2002)
Latências do reflexo trigêmino-facial e índices cefalométricos foram analisados em 30 voluntários adultos normais, de 3 diferentes raças, sendo 10 brancos, 10 negros e 10 orientais. Idades variaram de 15 a 59 anos, alturas de 1,6 a 1,8 m e pesos de 60 a 80 kg. Os reflexos trigêmino-faciais foram obtidos por estimulação elétrica unilateral do nervo supra-orbital e captação nos músculos orbicularis oculi, para análise quantitativa de 3 respostas, ipsolateral precoce (R1), ipsolateral tardia (R2i) e contralateral tardia (R2c). Índices cefalométricos foram obtidos multiplicando-se por 100 a razão entre maior diâmetro transverso e maior diâmetro sagital do crânio. As médias dos índices cefalométricos de cada grupo foram compatíveis com as respectivas características raciais. As respostas R1, R2i e R2c não mostraram diferenças de latências estatisticamente significativas entre as 3 diferentes raças analisadas neste estudo.

The blink reflex latencies and cephalometric indexes were analysed in 30 male volunteers from three different races, 10 white, 10 black, and 10 Oriental. Ages ranged from 15 to 59 years, height from 1,60 to 1,80 m, and weight from 60 to 80 kg. Blink reflexes were obtained after unilateral electric stimulation of the supraorbital nerve for quantitative analysis of 3 responses, early ipsilateral (R1), late ipsilateral (R2i) and late contralateral (R2c), obtained from the orbicularis oculi muscle. Cephalometric indexes were calculated by multiplying the ratio between the longer transverse and the longer sagital head diameters by 100. The R1, R2i and R2c latencies were consistent with other published papers revealing no differences between the different racial groups. The mean of the cephalometric indexes of each group were consistent with respective racial characteristics. This study revealed that there are no differences between R1, R2i and R2c latencies in the 3 different studied races.
Reflexo trigêmino-facial: comparação de medidas de latência em diferentes raças
Keywords: reflexo trigêmino-facial; raças; blink reflex; races